STATUS GIZI DAN STATUS KESEGARAN JASMANI PESERTA DIDIK SEKOLAH DASAR NEGERI BANUA PADANG KECAMATAN BUNGUR KABUPATEN TAPIN - Denker Sandra Amicetya (Lambung Mangkurat University, 2014)
Nutritional Status And The Status Of Physical Freshness Of Primary School Learners Banua Districts Of The Country, Lagerstroemia Tapin Regency.The purpose of this research is to determine the nutritional status and statuswithkeseg ran physical SDN Banua Padang District of Bungur Regency of Tapin. Research methods used in this research is quantitative descriptive technique of measurement and test. Populasi in this research is SDN Banua Padang District of Bungur Regency of Tapin Lagerstroemia. Lagerstroemia totalling 143 people. The research sample is learners classes V and VI which was 10-12 years amounted to 40 people. Sampling using the technique of sampling purpossive.Research results revealedthat overall nutritional status learners SDN Banua Padang District of Bungur Regency of Tapin. Lagerstroemia in the category either (B). D's to the status of physical freshness within the classification Being (S). Keywords: Nutritional Status, Status of Physical Freshness